Strategi Sumberdaya Manusia Dengan Faktor Determinan Kecemasan Kelompok Tani Akibat Dampak Covid 19/New Normal (Studi Pada Kelompok Tani desa di Urek-Urek Kec.Gondanglegi Kab.Malang) - Fatoni, Muchammad Arif; Djaelani, Abdul Kodir; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to identify and describe human resource strategies with the determinant factors of farmer group anxiety due to the impact of covid 19/new normal. This study uses a qualitative method. This type of research is by conducting case studies (case studies), natural observation (natural observation), centered interviews (focused interviews). The population of this study was the Farmer Group in the Urek-Urek Gondanglegi Village, Malang Regency, using purposive sampling. Sources of data obtained from interviews and using secondary data obtained from library materials, previous research, books and others. The result of this study is that the role of human resources for farmer groups in the village of Urek-Urek Gondanglegi is apparently inadequate and optimal so that it still provides internal and external obstacles. One effort that can help and facilitate the performance of farmer groups is to increase human resources, especially in the agricultural sector for farmer groups in Urek-Urek Village. Keywords: Determinant Factors Of Farmer Group Anxiety Due To The Impact Of Covid 19